An exploration of antigen expression of hepatitis C entry receptors on equine cells in relation to equine hepacivirus A - Sohrmann, Mascha (2022)
Equine hepacivirus A (EqHV) belongs to the family Flaviviridae and has been identified as the hepacivirus phylogenetically most closely related to Hepatitis C virus (HCV). Like HCV, EqHV is a hepatotropic virus that has been reported in over seventeen countries from six continents. However, much is still largely unknown about EqHV, such as its entry, pathogenesis and exact mode of transmission, although some cases of vertical transmission have been reported. The main four receptors used by HCV for viral entry to human hepatocytes are cluster of differentiation-81 (CD-81), occludin (OCLN), claudin-1 (CLDN-1) and scavenger receptor class B member 1 (SR-B1). This study investigated the presence of HCV entry receptors on equine cells and tissues, including equine hepatocytes, peripheral blood mononuclear cells (PBMCs), lymph node, placenta and liver using flow cytometry, immunofluorescence, immunocytochemistry and immunohistochemistry. CD81 was present in equine liver tissue, equine term placenta, equine lymph nodes and equine PBMCs, in particular on equine lymphocytes. OCLN was present in some neutrophils, hepatocytes as well as the nuclei of endothelial cells in the equine liver and some lymphoblasts within equine lymph nodes. This study has provided preliminary insights into the expression of putative EqHV receptors on equine tissues and cells and thus highlighted potential mechanisms of viral entry of EqHV into cells, which will hopefully aid in the understanding of its transmission.